Thomas Berdmore, dentist of His Majesty, George III, and dental calculus - Andreana, S; Andreana, G; Gonzalez, Y M; Ciancio, S (Journal of the history of dentistry, 1996)
Thomas Berdmore's book, Disorders of Deformities of the Teeth and Gums, presents examples of early concepts of preventive dentistry and treatment of periodontal diseases. Various aspects of dental calculus formation and composition are analyzed. Also the effects of periodontal disease as seen by Berdmore are discussed, and ways of treatment in 1770 summarized.